Mapping of Educational Resources of Central Jakarta Junior High School - Hamid Al Jufri (Journal of Social Science, 2023)
The problem of this research is that there are still many teachers who are not yet professional because teachers are the spearhead of a nation's progress. The purpose of this research is to find out the level of education, status, certification, and age of junior high school teachers in Central Jakarta. The population in this study were all teachers in Central Jakarta. Data collection techniques were carried out by means of documentation and questionnaires. In order to get an accurate assessment, the assessment of the results of the questionnaire is carried out with a descriptive quantitative assessment. The results of the study showed that there were still 194 high school level teachers, 633 auxiliary and honorary teachers, and 816 who had not been certified, and there was still a lack of young teachers. Based on the results of this study, it is suggested that public schools in Central Jakarta need to increase the level, status, and certification of teachers, and that there needs to be age consideration in accepting teachers.